2014
DOI: 10.1177/1070496514536395
|View full text |Cite
|
Sign up to set email alerts
|

Local Communities Vulnerability to Climate Change and Adaptation Strategies in Bukavu in DR Congo

Abstract: The analysis of vulnerabilities can help answer where and how society can best invest in vulnerability reduction. This study aimed at exploring vulnerability and adaptation strategies to climate change of local communities in Bukavu in DR Congo. Participatory action research was used in six villages from three collectivities around the Kahuzi Biega Park. Results showed that (a) perception of climate change depends on what people can see and feel about climate, (b) climate-related risks exacerbated existing pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 32 publications
2
45
2
1
Order By: Relevance
“…For example, in rainfed systems that are prone to drought, diversification of farm plot locations can take advantage of spatial variability in rainfall. The most common diversification strategy identified by the reviewed studies was to grow a variety of crops (Bryan et al 2009(Bryan et al , 2013Bele et al 2014;Westengen and Brysting 2014). Previous research demonstrated a positive correlation between crop diversity and production (Di Falco et al 2010).…”
Section: Crop Diversificationmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, in rainfed systems that are prone to drought, diversification of farm plot locations can take advantage of spatial variability in rainfall. The most common diversification strategy identified by the reviewed studies was to grow a variety of crops (Bryan et al 2009(Bryan et al , 2013Bele et al 2014;Westengen and Brysting 2014). Previous research demonstrated a positive correlation between crop diversity and production (Di Falco et al 2010).…”
Section: Crop Diversificationmentioning
confidence: 99%
“…The onset of the rainy season is crucial to the timing of rainfed crops: if a farmer plants too early, soil moisture will be insufficient for seed germination; if a farmer plants too late, intense rain might wash seed away (Reason et al 2005). Farmers in several SSA countries reported they shift crop planting dates in response to year-to-year variability in rainy season onset (Fosu-Mensah et al 2012;Bryan et al 2013;Sofoluwe et al 2011;Bele et al 2014). The main limitation is availability of accessible and accurate climate forecasts, which complement indigenous knowledge.…”
Section: Change In Planting Datesmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, we found few studies that quantify the role of green infrastructure in mitigating urban surface temperatures in sub-Saharan African cities (Schäffler and Swilling 2013;Bele et al 2014;Cavan et al 2014;UN-Habitat 2014). Therefore, the aim of this study is to assess the effect of green infrastructure on LSTs caused by urbanization in the BoboDioulasso during 1991-2013, using available geospatial data.…”
Section: Objectivesmentioning
confidence: 96%